POLA KONSUMSI DAN TINGKAT KETAHANAN PANGAN RUMAH TANGGA PETANI UBI KAYU DI KECAMATAN TERUSAN NUNYAI KABUPATEN LAMPUNG TENGAH - Karina Indira Putri; Ktut Murniati; Rabiatul Adawiyah (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2019)
This study aims to determine the consumption patternand level of household food security of cassava farmers and find out the relationship between consumption patterns and the level of household food security of cassava farmers. Determination of the location of the study, namely Gunung Batin Udik Village Terusan Nunyai District of Central Lampung Regency,is carried out by purposive method for this location is a center of cassava production. The samplesare77 cassava farmer households obtained by simple random sampling method. The data analytical method used in this study is descriptive statistical and qualitative descriptive analysis. The results showed that the Desirable Dietary Pattern (DDP) score of cassava farmer households is in the low category (61.62). The level of food security of cassava farmers is in poor condition and food insecurity. Food consumption patterns (DDP score) related to the level of food security. In a sense, the higher the food consumption pattern (DDP score), thebetter thefood security level.Key words: consumption patterns,food security, households